Increased nitrous oxide emissions from Arctic peatlands after permafrost thaw - Voigt, Carolina; Marushchak, Maija E.; Lamprecht, Richard E.; Jackowicz-Korczyński, Marcin; Lindgren, Amelie; Mastepanov, Mikhail; Granlund, Lars; Christensen, Torben R.; Tahvanainen, Teemu; Martikainen, Pertti J.; Biasi, Christina (Proceedings of the National Academy of Sciences - PNAS, 2017)
Permafrost in the Arctic is thawing, exposing large carbon and nitrogen stocks for decomposition. Gaseous carbon release from Arctic soils due to permafrost thawing is known to be substantial, but growing evidence suggests that Arctic soils may also be relevant sources of nitrous oxide (N₂O). Here we show that N2O emissions from subarctic peatlands increase as the permafrost thaws. In our study, the highest postthaw emissions occurred from bare peat surfaces, a typical landform in permafrost peatlands, where permafrost thaw caused a fivefold increase in emissions (0.56 ± 0.11 vs. 2.81 ± 0.6 mg N₂O m−2 d−1). These emission rates match those from tropical forest soils, the world’s largest natural terrestrial N₂O source. The presence of vegetation, known to limit N₂O emissions in tundra, did decrease (by ∼90%) but did not prevent thaw-induced N₂O release, whereas waterlogged conditions suppressed the emissions. We show that regions with high probability for N₂O emissions cover one-fourth of the Arctic. Our results imply that the Arctic N₂O budget will depend strongly on moisture changes, and that a gradual deepening of the active layer will create a strong noncarbon climate change feedback.